Recurrence of moderate to severe ulcerative colitis after fecal microbiota transplantation treatment and the efficacy of re-FMT: a case series - Dang, Xiao-Fei; Qing-Xi Wang; Yin, Zhao; Sun, Lin; Yang, Wei-Hua (BMC gastroenterology, 2020)
Ulcerative colitis (UC) is a chronic inflammatory bowel disease (IBD), the pathogenesis of which is complicated, and it is difficult to treat. In recent years, the emerging fecal microbiota transplantation (FMT) has shown good effects in UC treatment and is therefore accepted by increasing numbers of patients. Our hospital has carried out FMT since 2017, and has achieved good results in UC treatment. We have found in our clinical work that the efficacy of re-FMT after recurrence decreased. This is difference from reported literatures. In order to attract clinical attention, here we selected typical cases for analysis. Among all UC patients who received FMT in our hospital, 12 patients with moderate to severe UC were selected. They all received multiple FMT and were followed up for 52 weeks. Besides, none of them had other underlying diseases. Colonoscopy images of patients were presentated, SCCAI and UCDAI were used assess the effect of FMT. On the whole, FMT has a significant effect on moderate to severe UC. Of the 12 patients, 11 (91.7%) achieved a clinical response, 9 (75.0%) achieved clinical remission, and only one patient did not respond to FMT treatment. However, 6 patients relapsed within 52 weeks after remission, with a recurrence rate of 54.5%. Four of the six relapsed patients received FMT again, but the efficacy of FMT after relapse was significantly lower than that of the initial FMT. Fortunately, compared to before the initial FMT treatment, the severity of the disease after relapse was significantly reduced. FMT has a good effect on the relief of moderate to severe UC. However, the effect of FMT treatment after relapse is reduced. For patients who relapse after remission, the efficacy of FMT reapplication requires more experiments to verify.